2014
DOI: 10.1038/512365a
|View full text |Cite
|
Sign up to set email alerts
|

Earth systems: Model human adaptation to climate change

Abstract: We can no longer ignore feedbacks between global warming and how people respond, say Paul I. Palmer and Matthew J. Smith.to understand how people respond to their environment. But omitting human behaviour is like designing a bridge without accounting for traffic. DECISIONS, DECISIONSThere are two main scientific challenges to modelling socio-economic responses to climate change. The first is describing how humans make decisions. The second is describing the relationships between humans and the physical and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
81
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 7 publications
0
81
0
3
Order By: Relevance
“…We concur with Lahsen et al (1) there are other (perhaps better) examples than we chose to illustrate the tendency of global change scientists to presume a 'single, seamless concept of integrated knowledge' is realizable and desirable. Paul Palmer and Matthew Smith provide a recent one in Nature (2). We apologise if we misrepresented their article (3), and applaud their most recent efforts to detail how anthropology can help us better understand climate change (4).…”
Section: Towards a New Intellectual Climatementioning
confidence: 99%
“…We concur with Lahsen et al (1) there are other (perhaps better) examples than we chose to illustrate the tendency of global change scientists to presume a 'single, seamless concept of integrated knowledge' is realizable and desirable. Paul Palmer and Matthew Smith provide a recent one in Nature (2). We apologise if we misrepresented their article (3), and applaud their most recent efforts to detail how anthropology can help us better understand climate change (4).…”
Section: Towards a New Intellectual Climatementioning
confidence: 99%
“…Numerous studies, however, have shown that understanding individual and collective human behavior is also critical for managing natural resources (11,12) such as marine ecosystems (13,14). Socialecological system research responds to the need to incorporate humans as part of ecosystems by treating natural resource use as arising from linked systems of humans and nature, so-called social-ecological systems.…”
mentioning
confidence: 99%
“…To understand the impacts of climate change on human society it is imperative to measure anomalous behavioral responses as they coincide with hazards at the common spatiotemporal scales in which they occur (Palmer and Smith 2014). This is especially crucial where people are dependent on stable environmental conditions for livelihoods, and where both climate change and the burden of adaptation threaten human security and development (Adger et al 2014;Field et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Mobile operator data are updated in close to real-time and have a vast geographic reach. The data generated from mobile operators enable measurement of some characteristics of social networks, migration, and patterns of household economic behavior at a previously unprecedented scale (Bagrow et al 2011;Palmer and Smith 2014;Zolli 2012). Operator data has been used during relief operations after the Haiti 2010 earthquake (Bengtsson et al 2011;Lu et al 2012) and cholera outbreaks (Bengtsson et al 2015) and the Nepal 2015 earthquake (Wilson et al 2016), making them a very promising proxy indicator for measuring impacts of climate change, and weather extremes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation